IMPOLITENESS STRATEGY IN INSTAGRAM CYBERBULLYING: A CASE STUDY OF JENNIFER DUNN POSTED BY @LAMBE_TURAH - Fani Indrawan (ETNOLINGUAL, 2018)
Social media is used by most Indonesian people. Social media brings good and bad influence. One of the bad influences is cyberbullying. Cyberbullying that is found in Instagram is the most different from other social media. Instagram has become the source of hate campaign by the occurrence of gossip account. @Lambe_turah is one of the biggest gossip accounts in Indonesia. The posts in @Lambe_turah have triggered its followers to perform cyberbullying to the person in their post. The victim of cyberbullying who became the focus of this research was Jennifer Dunn. The aim of this study was to investigate the comments which contain cyberbullying by using impoliteness strategy proposed by Culpeper (2005). This study uses qualitative approach. It is shown by the data collection method which was done by examining documents. The analysis of this study was done by interpreting the collected data. The result showed that negative impoliteness was the most common impoliteness strategy to be used in cyberbullying. The second impoliteness strategy that was used in cyberbullying was bald on record. From both of these strategies, it could be concluded that cyberbullying tend to attack the addressee directly by using various types of statements.